Microtensile bond strength of CAD/CAM materials to dentin under different adhesive strategies - Bellan,Mariá Cortina (2017)
Abstract: The present study aimed to evaluate the microtensile bond strength (μTBS) of novel computer-aided design/computer-aided manufacturing (CAD/CAM) restorative materials to dentin using different adhesive strategies. Thirty-two crowns were milled using CAD/CAM materials (Vita Mark II as control, Vita Suprinity, Vita Enamic and Lava Ultimate) and luted to dentin using different resin cements (RelyX ARC, RelyX Unicem 2 and RelyX Ultimate). The specimens were stored in 100% relative humidity at 37°C for 24 h and sectioned. The samples (n = 16) with cross-sectional areas of approximately 0.90 mm2, were submitted to a μTBS test in a universal testing machine with a crosshead speed of 0.5 mm/min. The samples were analyzed with SEM to determinate the failure mode. According to 2-way ANOVA and Tukey's test (α=0.05), the interaction effect (material x luting strategy) was significant (p=0.001). Regardless of the luting strategy, a higher μTBS was obtained with Lava Ultimate and Vita Enamic, which were significantly different from Vita Mark II and Vita Suprinity (p<0.05). For Vita Mark II, Vita Suprinity, Vita Enamic, and Lava Ultimate, the μTBS obtained with RelyX Unicem 2 was not significantly different from that obtained with RelyX ARC or RelyX Ultimate. All groups obtained at least three types of failure. The adhesive strategy with self-adhesive resin cement was comparable to conventional resin cement with total-etch or self-etch adhesive techniques in the bond of novel CAD/CAM materials to dentin.